Spatiotemporal Analysis of the Bohai Sea Coastline Based on GIS and Remote Sensing - Feng, Qingyang (Transactions on Environment, Energy and Earth Sciences, 2024)
In recent years, the Bohai coastline has undergone significant changes. Due to sea reclamation and harbor construction driven by industrialization, the coastline has expanded significantly, bay areas have shrunk, and the types of coastal land use experienced huge changes. These alterations pose threats to the stability of coastal ecosystems. Remote sensing plays a crucial role in monitoring the spatiotemporal changes of coastlines, providing high-resolution images that are indispensable for coastal analysis. Based on remote sensing and GIS methods, this paper will analyze the spatiotemporal changes of the coastline from 1986 to 2016, identifying the drivers behind these changes. The study focuses on three main factors: coastline change, bay area change and land-use type change. It finds an increase of 1102.77 km in coastline length, a decrease of 1824 km² in the bay area, and a gradual replacement of natural shorelines with artificial ones and constructed lands, leading to severe degradation of coastal mudflat wetlands. These changes have resulted in impaired ecosystem services, habitat loss, and reduced biodiversity, threatening the stability of the coastal ecosystem.